RIOTs in Germany - constructing an interregional input-output table for Germany - Oliver Krebs (University of Tübingen, Faculty of Economics and Social Sciences, 2020)
This paper shows how to adapt recent methodological advances to derive a shipment based interregional input output table for 402 German counties and 26 foreign partners for 17 sectors that is, for national aggregates, cell-by-cell compatible with the WIOD tables. It far outperforms the standard approach of applying unit values to interregional shipments in replicating observed regional statistics and can be used for improved impact analysis and CGE model calibration. It thereby mitigates the surprising but problematic lack of regional German trade data in the analysis of both, regional effects of aggregate shocks such as trade agreements as well as network effects of regional policies. Moreover, the paper takes an in-depth look at the derived German production structure and trade network at the county level finding a surprisingly vast heterogeneity with respect to specialization, agglomeration and trade partners.
urn:nbn:de:bsz:21-dspace-990269
Keywords: R15; R12; F17; 330; Germany; regional trade; input-output tables; unit values; proportionality